Interaksi Sosial Pelaku Konversi Agama Etnik Cina - MARYAM YUSUF (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
The conflicts involve some parts of religius aspects or demensions like belief, rite, leadership, institution, knowladge, pratice, symbol, rationality and consequensces often occurd as the conflict-simbol at etnic. But on the orher hand there are some of Chinese at Ponorogo do conversion from their old belief to Islam. That is the phenomena will be increased to analyze based on emic prespective to comprehend the meaning of conversion. The main purpose of this research is to comprehend the meaning and motivations of conversion. The objective of this research are to analyze the phenomena of conversion proses, comprehend meaning and motivation meaning. To investigate the rationality of conversion from being Chinese. Secondly, it is to discover of converts the social and relegious behaviour of the conversion, in which the consequences of conversion to analyze and describe based on invetigation. It’s social interaction between converts and moslem (Javanese) and others. By using qualitative approach, emic perspective, interviewing some identified converts, observing religius social setting and reading document information this research carried out at Ponorogo district, this article discovered that the oneness of God Rationality or Tawhid Rationality. The converts in this case make comparation with their belief before Islam. They know about syari’at Islam and effort to do as well as possibleKEYWORD : Religius Conversion, Etnic Studies, Rationality